Peptide-polysaccharide conjugates with adjustable hydrophilicity/hydrophobicity as green and pH sensitive emulsifiers. (February 2017) - Yin, Baoru; Wang, Chaonan; Liu, Zhijia; Yao, Ping
Abstract: In this study, we used deamidated zein peptide-polysaccharide conjugates as emulsifiers to produce oil in water emulsions. Zein is insoluble in water. Its asparagine and glutamine residues changed to aspartic acid and glutamic acid residues and also zein was degraded during deamidation reaction in alkaline condition. Longer deamidation reaction produced more carboxyl groups and smaller peptides. The peptides with average molecular weights of 7.3, 5.5 and 4.0 kDa were obtained after 36, 96 and 144 h of the deamidation reaction, respectively. Dextran (Mw 16 kDa) and maltodextrin (Mw 3.0 kDa) were separately conjugated to the N-terminals of the peptides via Maillard reaction. The hydrophilicity/hydrophobicity of the peptide-polysaccharide conjugates can be adjusted by deamidation reaction time, number of conjugated polysaccharide molecules, polysaccharide molecular weight, and medium pH. The conjugates, in which about 65.4–90.6% of the peptides were conjugated with the polysaccharide, had prominent emulsification ability at acidic condition. The emulsions produced and stored at pH 4.0 and 4.5 were long-term stable. When the emulsions were stored at pH 7.4, at which the carboxyl groups were significantly deprotonated, demulsification happened. The oil layer appearance time changed from 2 days to more than 70 days; the time decreased with the increase of the conjugate hydrophilicity. This study demonstrates that the emulsions produced from the conjugates have pH sensitivity and adjustable stability. The deamidated zein peptide-polysaccharide conjugates, which synchronously possess natural moieties, adjustable hydrophilicity/hydrophobicity, smaller molecular weights and simpler structures compared with protein-polysaccharide conjugates, are excellent and green emulsifiers. Graphical abstract: Highlights: Deamidated zein peptide with pH sensitivity was produced by hydrolysis. Polysaccharide was conjugated to the N-terminal of the peptide. Hydrophilicity of the conjugate can be adjusted by four ways. The conjugate is good emulsifier at acidic condition. The emulsion stability at pH 7 is tunable by hydrophilicity of the conjugate.